Selection of Residence Based on Public Perception of Settlements as an Effort to Support the KOTAKU Program - Devi Triwidya Sitaresmi; Meidi Arisalwadi; Rina Noor Hayati (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
Currently, there are many programs from the government related to urban villages. One of them is Kampung Kota Baru Tengah in Balikpapan City, which is the location for the Community-Based Settlement Environmental Management program (KOTAKU Program). The socialization program is carried out with an approach to the informal community. Socialization through community media is the mainstay of the government so that existing programs can be realized properly in society. This study aims to see the similarity of perceptions regarding space as a place to live. Considering that a common perception is one of the first steps to achieving the success of the KOTAKU program, where a common perception of where to live will become the vision of development in residential areas so that people will be more consistent in implementing the KOTAKU program. This study uses Multidimensional Scaling (MDS) analysis, which will then map the perceptions of settlements. The results of the perception mapping formed show that individuals in each community have different perceptions of settlements. Based on perceptions of reconciliation grouping, we found that 51% chose identity as the main reason for staying and 48.5% chose location dependence as the main reason for staying. This perception formed in the community suggests that government strategies for environmental and housing improvement programs are advocated to reflect or strengthen people's sense of identity and place dependability. Strengthening this sense of identity can be linked to any development activity that can reflect local wisdom, while the location dependency aspect can be linked to improving settlement infrastructure.